2019
DOI: 10.1038/s41598-019-50813-w
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of an atypical LEA gene (IpLEA) from Ipomoea pes-caprae conferring salt/drought and oxidative stress tolerance

Abstract: Late embryogenesis abundant (LEA) proteins belong to a large family that exists widely in plants and is mainly involved in desiccation processes during plant development or in the response to abiotic stresses. Here, we reported on an atypical LEA gene (IpLEA) related to salt tolerance from Ipomoea pes-caprae L. (Convolvulaceae). Sequence analysis revealed that IpLEA belongs to the LEA_2 (PF03168) group. IpLEA was shown to have a cytoplasmic localization pattern. Quantitative reverse transcription PCR analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 54 publications
(100 reference statements)
1
20
0
Order By: Relevance
“…These genes have a major role in detoxification of ROS in the plant cell, which is extremely harmful as it causes lipid oxidation, DNA damage, and apoptosis. In agreement with our study, the role of protein detoxification has been documented in many plant species, i.e., Ipomoea batatas 18,88 , Ipomoea pes-caprae 89 , Arabidopsis thaliana 90 , Nicotiana tabacum 91 , Oryza sativa L. 92 and Solanum lycopersicum 93 . In addition, TSA genes are involved in the detoxification of reactive oxygen species (ROS), reactive sulfur species (RSS), and reactive nitrogen species (RNS).…”
Section: Discussionsupporting
confidence: 92%
“…These genes have a major role in detoxification of ROS in the plant cell, which is extremely harmful as it causes lipid oxidation, DNA damage, and apoptosis. In agreement with our study, the role of protein detoxification has been documented in many plant species, i.e., Ipomoea batatas 18,88 , Ipomoea pes-caprae 89 , Arabidopsis thaliana 90 , Nicotiana tabacum 91 , Oryza sativa L. 92 and Solanum lycopersicum 93 . In addition, TSA genes are involved in the detoxification of reactive oxygen species (ROS), reactive sulfur species (RSS), and reactive nitrogen species (RNS).…”
Section: Discussionsupporting
confidence: 92%
“…In this review, novel insights related to DHNs were generated that characterized their functional properties under the stress environment, as it is crucial to have an extensive understanding about their biochemical, physiological, and biological functions in plant stress management. A number of transgenic approaches have indicated that overexpression of group II LEA proteins in a wide range of plant species improves abiotic stress resistance [9].…”
Section: Group II Lea Proteins' Functional Heterogeneitymentioning
confidence: 99%
“…Group II LEA proteins were initially found in developing cotton (Gossypium hirsutum) embryos and are expressed in gymnosperms and angiosperms ubiquitously [8]. A positive association between the accumulation of group II LEA proteins and environmental stresses such as drought, heat, freezing, and salinity has been outlined in a number of studies [9]. However, in relation to contemporary genomics, these studies need to be reviewed and necessitate the generation of additional important structural, physicochemical, molecular, and functional characterization of group II LEA proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, LEA-like proteins are also found in a variety of organisms, such as anhydrobiotic nematodes [111,112], brine shrimp [113], rotifers [114,115], and some bacterial species [108]. Although LEAs were first described in embryonic tissues, thirty years of intensive research showed that the expression of LEA genes is also significantly induced in vegetative organs (i.e., callus, flowers, roots, leaves, buds) under abiotic stresses such as desiccation, salinity, and cold [116][117][118][119][120].…”
Section: Late Embryogenesis Abundant (Lea) Proteins Accumulationmentioning
confidence: 99%